Influence of Menopausal Status on the Symptom Experience of Women Before Breast Cancer Surgery. Issue 4 (July 2018) - Mazor, Melissa; Cataldo, Janine K.; Lee, Kathryn; Dhruva, Anand; Paul, Steven M.; Smoot, Betty J.; Dunn, Laura B.; Levine, Jon D.; Mastick, Judy; Conley, Yvette P.; Miaskowski, Christine
Abstract : Background: Breast cancer treatments can change women's hormonal milieu and alter their symptom experience. Little is known about associations between menopausal status and menopausal symptoms in women with breast cancer before surgery. Objective: The purpose of this study was to evaluate for differences in occurrence, severity, and distress of symptoms between premenopausal and postmenopausal women before breast cancer surgery. Methods: A total of 312 women with breast cancer completed the Menopausal Symptoms Scale, a self-report measure that evaluated the occurrence, severity, and distress of 46 common symptoms associated with menopause. Regression analyses were used to evaluate for between-group differences in these symptoms. Results: Of the 312 patients enrolled, 37.4% (n = 116) were premenopausal, and 62.6% (n = 196) were postmenopausal. In the multivariate analysis that adjusted for 7 covariates, premenopausal patients reported higher occurrence rates for urinary frequency ( P = .006) and reported lower occurrence rates for joint pain/stiffness ( P = .011), difficulty falling asleep ( P = .025), and vaginal dryness ( P = .002). A significant interaction was found between age and menopausal status for hot flashes ( P = .002), wake during the night ( P = .025), and headache ( P = .040). Conclusion: Regardless of menopausal status, women reported high occurrence rates for several menopausal symptoms. Associations between some symptom occurrence rates and menopausal status depended on the patients' age. Implications for Practice: As part of a preoperative symptom assessment, clinicians need to consider a woman's menopausal status and salient demographic and clinical characteristics. The identification of women with a higher symptom burden will assist with more effective management. Abstract : Supplemental digital content is available in the text.